PENGARUH VARIETAS DAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAK CHOI (Brassica chinensis L.) - Adi Gunawan; Susylowati Susylowati (DINAMIKA PERTANIAN, 2013)
The experiment was carried out to obtain the variety of pak choy which shows the best respond on the urea fertilizer and, to determine urea dosage that caused the highest growth and yield of pak choy, also interaction between variety and urea fertilizer. The experiment was conducted in Sempaja, Samarinda from November to December, 2010. The Randomized Complete Block as Design, with factorial analysis 2 x 4 was used in the experiment. Each treatment was replicated three times. The first factor was pak choy varieties (V) consisting of two varieties, i.e.: v1 (Green) and v2 (White). The second factor was urea fertilizer dosage (U) consisting of four levels, i. e.: u0 (without urea); u1 (40 kg urea ha-1); u2 (80 kg urea ha-1) and u3 (120 kg urea ha-1). The statistical analysis showed that White variety gave the best result on the growth and yield than Green variety, with fresh weight was 22.24 Mg ha-1; The urea fertilizer 120 kg urea ha-1 dosage gave the best result on the growth and yield, with fresh weight is 23.36 Mg ha-1; while the interaction between two Factors (variety and Urea) was not significantly different on all variables observed. The orthogonal polynomial analysis showed that the relationship between urea fertilizer dosage (x) and fresh weight ha-1 (y) was linier, with equation of regression was ŷ = 13.675 + 0.082x, and correlation coefficient (r ) = 0.98.